Water hardening inorganic semaphore composition
The introduction of uncoated grinding glass or ceramic fibers with low alkali oxide content into hydraulic inorganic cement compositions addresses the issues of crack formation and electrical insulation in encapsulating electronic components, resulting in enhanced protection and reliability.
Patent Information
- Application Number
- JP2024556455
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-05-02
- Filing Date
- 2023-04-18
- Publication Date
- 2025-04-16
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing hydraulic inorganic cement compositions used for encapsulating electronic components often suffer from a high tendency to crack and inadequate electrical insulation, which can compromise the reliability and performance of the encapsulated components.
A hydraulically hardened inorganic cement composition containing uncoated grinding glass fibers or ceramic fibers with low alkali oxide content is developed. This composition, when mixed with water, forms a sealing compound that reduces crack formation and enhances electrical insulation.
The use of the described cement composition results in encapsulation bodies with reduced crack formation and improved electrical insulation properties, effectively protecting electronic components and ensuring their reliable operation.
Smart Images

Figure 2025511591000001 
Figure 2025511591000002 
Figure 2025511591000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a hydraulic mineral cement composition which can be mixed with water to produce an aqueous hydraulic mineral cement preparation which can be used to produce a hydraulically set mineral cement composition, in particular in the form of an encapsulant for electronic components. Summary of the Invention [Problem to be solved by the invention]
[0002] As used herein, the term "water-curing" includes curing in the presence of water or after the addition of water.
[0003] A distinction is made here between hydraulically curable inorganic cement compositions, aqueous, hydraulically curable inorganic cement preparations and hydraulically cured inorganic cement compositions. Aqueous, hydraulically curable inorganic cement preparations, in particular in the form of viscoelastic, e.g. pasty or flowable compounds (also called "cement pastes or cement glues"), can be produced from hydraulic inorganic cement compositions by mixing the latter with water. The aqueous, hydraulically curable inorganic cement preparations can then be cured and dried in water after their application to form hydraulically cured inorganic cement compositions in the form of hard solids, also called "cement stones". Such hydraulically cured inorganic cement compositions are substantially water-insoluble, i.e. substantially or completely water-insoluble.
[0004] As used herein, the term "electronic components" includes passive electronic components as well as, inter alia, semiconductor modules and, among the latter, electronic assemblies.
[0005] In the present specification, a semiconductor module is understood to mean an electronic assembly comprising at least one substrate (as circuit carrier), at least one semiconductor component (semiconductor) and, optionally, at least one passive electronic component. The at least one semiconductor component itself may be partially or completely pre-encapsulated, for example with an epoxy resin-based encapsulant.
[0006] The term "electronic assembly" is used herein. An electronic assembly in the context of the present invention comprises at least one substrate and at least one electronic component mechanically and electrically connected thereto. The mechanical and electrical connection can be a conductive soldering, sintering, and / or adhesive connection. Furthermore, such electronic assemblies can comprise elements that serve the electrical connection, such as bonding ribbons, bonding wires, clips, spacers, and / or foils. Examples of electronic assemblies, framed or unframed, include discrete components such as power discretes, power modules, voltage converters, and certain sensors.
[0007] Examples of substrates include IMS substrates (insulated metal substrates), AMB substrates (active metal brazed substrates), metal ceramic substrates such as DCB substrates (direct copper bonded substrates), ceramic substrates, PCBs (printed circuit boards), and lead frames.
[0008] Electronic components can be divided into active electronic components and passive electronic components.
[0009] Examples of active electronic components include diodes, LEDs (light emitting diodes), dies (semiconductor chips), IGBTs (insulated-gate bipolar transistors), ICs (integrated circuits), and MOSFETs (metal-oxide-semiconductor field-effect transistors).
[0010] Examples of passive electronic components include base plates, heat sinks, connectors, resistors, capacitors, inductors, antennas, transformers, throttles, coils, and sensors that do not form part of an electronic assembly.
[0011] The object of the present invention was to provide a hydraulic inorganic cement composition comprising inorganic fibers from which an aqueous cement sealing compound can be produced for producing seals for electronic components. In addition to a reduced tendency to form cracks thanks to the inorganic fibers, the seals should be characterized by a high electrical insulating effect.
[0012] Hydraulic inorganic cement compositions containing inorganic or glass fibers are disclosed, for example, in EP 1 044 942 (A1), WO 2015 / 067441 (A1) and WO 2015 / 193035 (A1).
[0013] It has been shown that the object can be achieved by providing a hydraulic inorganic cement composition containing uncoated comminuted glass fibers of low alkali oxide or alkali oxide free glass and / or uncoated comminuted ceramic fibers of low alkali oxide or alkali oxide free ceramic.
[0014] The term "alkali oxides" as used herein refers specifically to the alkali metal oxides commonly used in the glass art, namely lithium oxide, sodium oxide and potassium oxide.
[0015] The uncoated comminuted glass fibres made of low-alkali oxide or alkali oxide-free glass are made in particular of glass containing <5% by weight, preferably <2% by weight, particularly preferably <1% by weight, of alkali oxide.
[0016] It is important for the present invention that the glass of the uncoated ground glass fibers is low in or free of alkali oxides, in particular <5% by weight, preferably <2% by weight, particularly preferably <1% by weight of alkali oxides. They may also be quartz glass fibers. Preferably, the fibers consist of borosilicate glass, aluminosilicate glass or aluminium borosilicate glass, each with a correspondingly low or free alkali oxide content.
[0017] It is also important to the present invention that the glass fibers be uncoated.
[0018] The uncoated comminuted glass fibres may have a number average fibre length in the range of, for example, 20 μm to 1000 μm, preferably 40 μm to 600 μm, in particular 40 μm to 300 μm, and have a diameter in the range of, for example, 5 μm to 50 μm, preferably 10 μm to 20 μm, respectively.
[0019] Number average fiber length is mentioned several times in this specification. It can be determined, for example, using the FASEP® ECO system from IDM Systems, Helga Mayr, 64297 Darmstadt.
[0020] Uncoated milled glass fibers can be produced by milling corresponding cut or chopped glass fiber strands and are commercially available.
[0021] The uncoated comminuted ceramic fibers, which consist of low-alkali oxide or alkali oxide-free ceramics, in particular consist of ceramics having a purity of >98% by weight.
[0022] It is important to the present invention that the ceramic of the uncoated milled ceramic fibers have a purity of >98% by weight.
[0023] It is also important to the present invention that the ceramic fibers be uncoated.
[0024] The uncoated comminuted ceramic fibers are particularly those selected from the group consisting of aluminum oxide ceramic fibers, aluminum nitride ceramic fibers, silicon nitride ceramic fibers, silicon dioxide ceramic fibers, silicon carbide ceramic fibers and boron nitride ceramic fibers, each having a purity of >98% by weight.
[0025] The uncoated comminuted ceramic fibers may have a number average fiber length in the range of, for example, 20 μm to 1000 μm, preferably 40 μm to 600 μm, in particular 40 μm to 300 μm, and each have a diameter in the range of, for example, 5 μm to 50 μm, preferably 10 μm to 20 μm.
[0026] Uncoated milled ceramic fibers can be produced by milling corresponding cut or chopped ceramic fiber strands and are commercially available.
[0027] The hydraulic inorganic cement composition according to the invention comprises 5% to 15%, preferably 3% to 8% by weight of uncoated pulverized glass fibers, in particular made of glass with a proportion of alkali oxides of <5%, preferably <2%, particularly preferably <1%, by weight, and / or uncoated pulverized ceramic fibers selected from the group consisting of aluminium oxide ceramic fibers, aluminium nitride ceramic fibers, silicon nitride ceramic fibers, silicon dioxide ceramic fibers, silicon carbide ceramic fibers and boron nitride ceramic fibers, each having a purity of >98% by weight. Preferably, the hydraulic inorganic cement composition comprises glass fibers of said type, and in particular the latter alone, i.e. without the simultaneous presence of ceramic fibers of said type.
[0028] The hydraulic inorganic cement composition according to the invention in powder form can be converted into an aqueous hydraulic preparation that can be used as a sealing compound by mixing with water. The aqueous sealing compound can be used to produce a hydraulically hardened seal for electronic components.
[0029] The hydraulic inorganic cement composition according to the invention comprises, in addition to the glass fibres and / or the ceramic fibres, a possible non-fibrous particulate filler and a possible further component, a hydraulic inorganic cement. It is a powder. The particles of the cement powder can have an absolute particle size, for example, in the range of up to 1 mm. The hydraulic inorganic cement can be, for example, a Portland cement, a high alumina cement, a magnesium oxide cement or a phosphate cement known to the person skilled in the art. Phosphate cements, such as zinc phosphate cements or especially magnesium phosphate cements, are preferred. The hydraulic inorganic cement can, for example, constitute 2% to 95% by weight, preferably 3% to 40% by weight, of the hydraulic inorganic cement composition according to the invention.
[0030] The hydraulic inorganic cement composition according to the invention may in particular consist of the following components: (a) 2% to 95% by weight, preferably 3% to 40% by weight, of a cement selected from the group consisting of Portland cement, high alumina cement, magnesium oxide cement and phosphate cement; (b) 5% to 15% by weight, preferably 3% to 8% by weight, of uncoated comminuted glass fibers with a proportion of alkali oxide of <5% by weight, preferably <2% by weight, particularly preferably <1% by weight, and / or uncoated comminuted ceramic fibers selected from the group consisting of aluminum oxide ceramic fibers, aluminum nitride ceramic fibers, silicon nitride ceramic fibers, silicon dioxide ceramic fibers, silicon carbide ceramic fibers and boron nitride ceramic fibers, each having a purity of >98% by weight, (c) 0% to 90% by weight, preferably 40% to 80% by weight, of at least one non-fibrous particulate filler; (d) 0% to 30% by weight, preferably 2% to 15% by weight, of at least one component other than components (a) to (c). Components (a) to (d) total 100% by weight of the hydraulic inorganic cement composition according to the present invention. In other words, the hydraulic inorganic cement composition according to the present invention can consist of components (a) and (b), or of components (a), (b) and (c), or of components (a), (b) and (d), or of components (a), (b), (c) and (d).
[0031] Component (a) is a hydraulic inorganic cement. It is a powder. The cement powder particles can have an absolute particle size, for example, in the range of up to 1 mm. The hydraulic inorganic cement is selected from the group consisting of Portland cement, high alumina cement, magnesium oxide cement, and phosphate cement. Component (a) is preferably a phosphate cement, for example a zinc phosphate cement, or in particular a magnesium phosphate cement.
[0032] Particularly preferred phosphate cements as component (a) are (a1) 10% to 90% by weight, preferably 30% to 60% by weight, of at least one hydrogen phosphate selected from the group consisting of monohydrogen phosphates and dihydrogen phosphates of magnesium, calcium, and aluminum; and (a2) 90% to 10% by weight, preferably 70% to 40% by weight, of at least one compound selected from the group consisting of oxides, hydroxides and oxide hydrates of magnesium, calcium, iron, zinc, zirconium, lanthanum and copper. The sum of the weight percentages of components (a1) and (a2) is equal to 100% by weight of component (a).
[0033] Component (a1) is at least one substance selected from the group consisting of magnesium monohydrogen phosphate, calcium monohydrogen phosphate, aluminum monohydrogen phosphate, magnesium dihydrogen phosphate, calcium dihydrogen phosphate and aluminum dihydrogen phosphate. In other words, it is at least one hydrogen phosphate selected from the group consisting of monohydrogen phosphate and dihydrogen phosphate of magnesium, calcium and aluminum. In particular, it is at least one hydrogen phosphate selected from the group consisting of monohydrogen phosphate and dihydrogen phosphate of magnesium and aluminum.
[0034] Component (a1) is for example a powder having an absolute particle size in the range up to 1 mm.
[0035] Component (a2) is at least one compound selected from the group consisting of oxides, hydroxides and oxide hydrates of magnesium, calcium, iron, zinc, zirconium, lanthanum and copper, in particular at least one compound selected from the group consisting of magnesium oxide, magnesium hydroxide, zirconium oxide, zirconium oxide hydrate and zirconium hydroxide, with magnesium oxide being particularly preferred.
[0036] Component (a2) is for example a powder having an absolute particle size in the range up to 1 mm.
[0037] To avoid unnecessary length, see above regarding component (b).
[0038] Optionally, but preferably present, component (c) is at least one non-fibrous particulate filler which may be selected from the group consisting of mono-, oligo- and polyphosphates, in particular of magnesium, calcium, barium and aluminium; calcium sulfate; barium sulfate; silicates, mono- and double salts containing calcium, aluminium, magnesium, iron and / or zirconium; aluminates, mono- and double salts containing calcium, magnesium and / or zirconium; titanates, mono- and double salts containing calcium, aluminium, magnesium, barium and / or zirconium; zirconates, mono- and double salts containing calcium, aluminium and / or magnesium; zirconium dioxide; titanium dioxide; aluminium oxide; silicon dioxide, in particular in the form of silica and quartz; silicon carbide; aluminium nitride; boron nitride and silicon nitride. A distinction is made between mono- and double salts of silicates, aluminates, titanates and zirconates. What is meant by double salts are not complex compounds, but rather silicates, aluminates, titanates, and zirconates that have more than one cation, such as calcium aluminum silicate, lead zirconate titanate, etc.
[0039] Component (c) is for example a powder having an absolute particle size in the range up to 1 mm.
[0040] Optional component (d) is one or more components different from components (a)-(c), such as flow improvers, set retarders (pot life extenders), defoamers, hydrophobizing agents, additives that affect surface tension, wetting agents, and adhesion promoters.
[0041] The hydraulic inorganic cement composition according to the invention, in particular consisting of components (a), (b), preferably further (c) and optionally (d), may be present as a one-component powder composition or in the form of two or more powder components, i.e. different separate components (which have to be stored separately or which are stored separately). In the case of a two-component or multi-component composition, the components comprise all components together, i.e. in particular components (a) and (b), and / or (a) to (c), (a) to (d), or (a), (b) and (d). The two or more components are stored separately from one another until they are used to produce the aqueous hydraulic inorganic cement preparation. In this case, it may be particularly preferred to store components (a1) and (a2) at least substantially separated from one another.
[0042] The aqueous hydraulic inorganic cement preparation can be produced from the hydraulic inorganic cement composition according to the invention, which may be in one-component, two-component or multi-component powder form, by mixing with water. In the case of a two-component or multi-component system, the components can be mixed first to form a one-component hydraulic inorganic cement composition and then mixed with water. However, it is also possible to mix only one, some or all of the components first with water, for example to form a paste, and then further mixing can be carried out to form the aqueous hydraulic inorganic cement preparation. Such an aqueous hydraulic inorganic cement preparation can be used to produce a hydraulically set inorganic cement composition, in particular in the form of an encapsulant for electronic components, which after its application can be hydraulically set and dried to form a hydraulically set inorganic cement composition in the form of a hard solid. The hard solid body can in particular be the encapsulant for electronic components.
[0043] The aqueous hydraulic inorganic cement preparations obtainable from the hydraulic inorganic cement composition according to the invention by mixing with water can have a water content of, for example, 6% to 25% by weight.
[0044] The viscosity of a freshly produced (within 5 minutes of completion) aqueous hydraulic inorganic cement preparation may for example be in the range of 0.5 Pa·s to 20 Pa·s (measured by rotational viscometry, plate-plate measurement, plate diameter 25 mm, measuring gap 1 mm, sample temperature 20°C).
[0045] As mentioned above, the aqueous hydraulic inorganic cement formulation can be used as an aqueous sealing compound for electronic components. For the sake of brevity, the term "aqueous sealing compound" is used below instead of "aqueous hydraulic inorganic cement formulation".
[0046] A water-based sealing compound can be used to produce a water-cured encapsulant for electronic components. The manufacturing process includes the following steps: (1) providing an electronic component to be encapsulated; (2) providing an aqueous sealing compound prepared by mixing an aqueous hydraulic inorganic cement composition according to the present invention with water; (3) encapsulating the electronic component provided in step (1) with the water-based encapsulating compound provided in step (2); and (4) After completion of step (3), water curing the water-based sealing compound that encapsulates the electronic components.
[0047] In step (1), an encapsulated electronic component is provided. Regarding the term "electronic component", see above.
[0048] Regarding step (2), see above.
[0049] Preferably, step (3) is carried out within 60 minutes, preferably within 10 minutes, of completing step (2), or immediately after completing the preparation of the aqueous sealing compound.
[0050] In step (3), the electronic component provided in step (1) is coated with the water-based encapsulating compound provided in step (2). Preferred application methods are casting, dipping and injection molding (transfer molding). Casting can be performed using conventional methods known to those skilled in the art, for example by gravity-assisted casting, vacuum-assisted casting or pressure-assisted casting (compression molding). It may be suitable to surround the electronic component to be encapsulated in a half-shell mold and then fill it with the water-based encapsulating compound. The encapsulation can be performed as a partial encapsulation or a complete encapsulation. For example, when encapsulating a semiconductor module, the encapsulating compound can partially or completely encapsulate the electrical contact elements connected to the semiconductor component, such as the bonding wires, ribbons and / or substrate. Partial encapsulation means that one or more contact elements are incompletely encapsulated and / or one or more contact elements are not encapsulated, whereas complete encapsulation means that all contact elements are completely encapsulated. However, the casting can also be performed such that the encapsulating compound is formed as a "glob-top" as known to those skilled in the art.
[0051] In step (4) following step (3), the water-based sealing compound encapsulating the electronic components is water-cured. Of course, water-curing has already started from the moment the water-based sealing compound is produced, i.e. already during or after completion of step (2).
[0052] Water curing may be carried out under ambient conditions, for example at ambient temperatures ranging from 20° C. to 25° C., and may take, for example, 1 minute to 6 hours. For shorter times, higher temperatures may be used. For example, water curing may be carried out at object temperatures of 30° C. to less than 100° C., and is completed within a few seconds to an hour.
[0053] Water curing is followed by drying of the sealant to remove chemically unbound water from the water-cured inorganic cement composition. This can be done later in the process, but it may also be desirable to follow water curing with forced drying to dehydrate, for example at object temperatures of 80°C to 300°C for 0.5 to 6 hours, and may be desirable to go through several temperature stages. Drying can be done with vacuum assistance. EXAMPLES
[0054] A) Preparation of the aqueous hydraulic inorganic cement preparation Example 1 according to the invention: 7 parts by weight of magnesium oxide powder, 2 parts by weight of magnesium dihydrogen phosphate powder, 4 parts by weight of 2-imidazolidinone, 6 parts by weight of uncoated aluminum borosilicate glass fibers having less than 2% by weight of alkali oxide and having a number average fiber length of 50 μm and a diameter of 15 μm, 66 parts by weight of zirconium silicate having a maximum particle size of 100 μm, and 15 parts by weight of water were mixed to form an aqueous cement preparation.
[0055] Example 2 according to the invention: The procedure was the same as in Example 1, except that uncoated aluminum borosilicate glass fibers with less than 2% by weight of alkali oxide were used, with a number average fiber length of 190 μm and a diameter of 15 μm.
[0056] Comparative Example 3: The procedure was the same as in Example 1, except that silane-coated aluminum borosilicate glass fibers with a number average fiber length of 210 μm and a diameter of 15 μm were used.
[0057] B) Evaluation of the electrical insulation properties of hydraulic inorganic cement compositions produced from the aqueous hydraulic inorganic cement preparations according to Examples 1-3 Five test cells were first constructed to evaluate the electrical insulation properties of the hydraulically hardened inorganic cement compositions. For this purpose, one double-sided metallized copper-aluminum oxide ceramic substrate (DCB, area 27×38 mm, thickness of copper metallization 0.3 mm, thickness of aluminum oxide ceramic: 0.38 mm, surrounding non-metallized aluminum oxide edge 0.5 mm) was glued to the center of each of five round aluminum plates (diameter 55 mm, edge height 15 mm) using double-sided copper adhesive tape (length×width×thickness: 27±1 mm×21±1 mm×0.12 mm). Another copper adhesive tape (length×width×thickness: 50 mm×12 mm×0.11 mm) was glued in an L-shape to the upper copper foil of each DCB substrate (length of glued portion 10 mm, length of bent portion 40 mm).
[0058] Subsequently, 18±0.2 g of the aqueous hydraulic inorganic cement formulations of Examples 1-3 were weighed into the aluminum trays constructed as described above. Each cement formulation was ensured to completely cover each DCB substrate and flow over the edge of the aluminum tray. The folded portion of the copper adhesive tape attached to the surface of the DCB substrate protruded vertically from the cement formulation.
[0059] The test cells were then left at 20° C. for 2 hours to allow the water hardening of each cement preparation, followed by a temperature treatment in a laboratory oven, for which the temperature of the oven was increased from 20° C. to 90° C. at a heating rate of 1° C. / min and held at 90° C. for 1 hour. The temperature of the oven was then increased to 160° C. at a heating rate of 1° C. / min and held at 160° C. for 1 hour. The samples were then cooled to 20° C. at a rate of 1° C. / min.
[0060] To determine the electrical insulation properties, so-called dielectric strength measurements were carried out for each of the five test cells using a TPS 652-714 measuring device from Schuster Elektronik GmbH. For this purpose, a direct current was applied with the measuring device between the aluminum shell, which was connected to the lower copper foil of the DCB substrate via a copper adhesive tape, and the copper adhesive tape protruding from the cement composition attached to the upper copper foil of the DCB substrate. First, 100 V was applied for 1 second, which was gradually increased to 4000 V according to the instructions given in table 1. As soon as a leakage current of ≧2 mA was recorded, this was interpreted as a dielectric breakdown and the test was terminated. For the test cells cast with the cement formulations according to the invention according to examples 1 and 2, the voltage could be increased up to 4000 V without recording any leakage current. As a result, these cement compositions showed good electrical insulation properties and high electrical resistance, respectively. In contrast, in the test cells cast with the cement formulation according to comparative example 3, a leakage current of >2 mA was already detected at a voltage of 1200 V.
[0061] [Table 1]
Claims
1. A hydraulic inorganic cement composition comprising uncoated comminuted glass fibers of low alkali oxide or alkali oxide free glass and / or uncoated comminuted ceramic fibers of low alkali oxide or alkali oxide free ceramic.
2. 2. The hydraulic inorganic cement composition according to claim 1, comprising 5% to 15% by weight of uncoated pulverized glass fibers consisting of glass with a proportion of alkali oxides of <5% by weight, and / or uncoated pulverized ceramic fibers selected from the group consisting of aluminum oxide ceramic fibers, aluminum nitride ceramic fibers, silicon nitride ceramic fibers, silicon dioxide ceramic fibers, silicon carbide ceramic fibers and boron nitride ceramic fibers, each having a purity of >98% by weight.
3. 3. A hydraulic inorganic cement composition according to claim 1 or 2, which comprises in addition to said glass and / or ceramic fibres, possible non-fibrous particulate fillers and possible further components a hydraulic inorganic cement.
4. 4. The hydraulic inorganic cement composition of claim 3, wherein the hydraulic inorganic cement is a Portland cement, a high alumina cement, a magnesium oxide cement, or a phosphate cement.
5. 5. The hydraulic inorganic cement composition according to claim 3 or 4, wherein the hydraulic inorganic cement comprises 2% to 95% by weight of the hydraulic inorganic cement composition.
6. (a) 2% to 95% by weight of a cement selected from the group consisting of portland cement, high alumina cement, magnesium oxide cement, and phosphate cement; (b) 5% to 15% by weight of uncoated comminuted glass fibers consisting of glass having a proportion of alkali oxides of <5% by weight, and / or uncoated comminuted ceramic fibers selected from the group consisting of aluminum oxide ceramic fibers, aluminum nitride ceramic fibers, silicon nitride ceramic fibers, silicon dioxide ceramic fibers, silicon carbide ceramic fibers, and boron nitride ceramic fibers, each having a purity of >98% by weight; (c) 0% to 90% by weight of at least one non-fibrous particulate filler; (d) 0% to 30% by weight of at least one component other than components (a) to (c), A hydraulic inorganic cement composition, wherein the total of components (a) to (d) is 100% by weight.
7. Component (a) is (a1) 10% to 90% by weight of at least one hydrogen phosphate selected from the group consisting of monohydrogen phosphates and dihydrogen phosphates of magnesium, calcium, and aluminum; (a2) 90% to 10% by weight of at least one compound selected from the group consisting of oxides, hydroxides, and oxide hydrates of magnesium, calcium, iron, zinc, zirconium, lanthanum, and copper; 7. The hydraulic inorganic cement composition according to claim 6, wherein the sum of the weight percentages of components (a1) and (a2) is 100 weight percent.
8. 8. The hydraulic inorganic cement composition according to any one of claims 1 to 7, wherein the uncoated crushed glass fibres have a number average fibre length in the range of 20 μm to 1000 μm with a diameter in the range of 5 μm to 50 μm.
9. 9. The hydraulic inorganic cement composition according to any one of claims 1 to 8, wherein the uncoated crushed glass fibers are selected from the group consisting of quartz glass fibers, borosilicate glass fibers, aluminosilicate glass fibers, and aluminoborosilicate glass fibers.
10. 10. The hydraulic inorganic cement composition according to any one of claims 1 to 9, wherein the uncoated pulverized ceramic fibres have a number average fibre length in the range of 20 μm to 1000 μm with a diameter in the range of 5 μm to 50 μm.
11. A hydraulic inorganic cement composition according to any one of claims 1 to 10, in the form of a one-component powder composition or of two or more different separate powder components.
12. 12. An aqueous hydraulic inorganic cement preparation produced by mixing the hydraulic inorganic cement composition according to any one of claims 1 to 11 with water.
13. 13. Use of the aqueous hydraulic inorganic cement preparation according to claim 12 for producing a hydraulic inorganic cement composition in the form of an encapsulant for electronic components.
14. 1. A method for producing a water-cured encapsulant for an electronic component, comprising the steps of: (1) providing an electronic component to be encapsulated; (2) providing an aqueous sealing compound prepared by mixing the hydraulic inorganic cement composition according to any one of claims 1 to 11 with water; (3) encapsulating the electronic components provided in step (1) with the water-based encapsulating compound provided in step (2); (4) after completion of step (3), water curing the water-based sealing compound that encapsulates the electronic component.
Citation Information
Patent Citations
Glass fiber reinforced composition containing glass powder
JP1978081526A
Method for manufacturing a rigid heat-insulating and fire-resistant material having open porous sections, and the material manufactured thereby.
JP1994506437A
Method for manufacturing inorganic formed product
JP2002187761A
Semiconductor module with encapsulation cement covering semiconductor components
JP2016535464A
Semiconductor module including a encapsulation compound covering at least one semiconductor component
JP2017520111A